2019
DOI: 10.1088/1741-2552/ab377d
|View full text |Cite
|
Sign up to set email alerts
|

A BCI based visual-haptic neurofeedback training improves cortical activations and classification performance during motor imagery

Abstract: Objective. We proposed a brain–computer interface (BCI) based visual-haptic neurofeedback training (NFT) by incorporating synchronous visual scene and proprioceptive electrical stimulation feedback. The goal of this work was to improve sensorimotor cortical activations and classification performance during motor imagery (MI). In addition, their correlations and brain network patterns were also investigated respectively. Approach. 64-channel electroencephalographic (EEG) data were recorded in nineteen healthy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 43 publications
0
33
1
Order By: Relevance
“…There are multiple improvements in the field that suggest motor imagery learning among novice BCI users; for example, it has been shown that realistic feedback from humanlike bodies and the feeling of embodiment improves the modulation of brain activity needed for motor imagery (Alimardani et al, 2018;Penaloza et al, 2018;Choi et al, 2020). Furthermore, visual guidance in virtual reality (Liang et al, 2016;Coogan andHe, 2018), gamification (de Castro-Cros et al, 2020), and multimodal visual-haptic feedback (Wang et al, 2019) can improve learning of MI-BCI. Improving the training conditions might reveal a more robust difference between (in-)efficient learners and thereby provide more valid evidence for the impacting variables on MI-BCI.…”
Section: Future Researchmentioning
confidence: 99%
“…There are multiple improvements in the field that suggest motor imagery learning among novice BCI users; for example, it has been shown that realistic feedback from humanlike bodies and the feeling of embodiment improves the modulation of brain activity needed for motor imagery (Alimardani et al, 2018;Penaloza et al, 2018;Choi et al, 2020). Furthermore, visual guidance in virtual reality (Liang et al, 2016;Coogan andHe, 2018), gamification (de Castro-Cros et al, 2020), and multimodal visual-haptic feedback (Wang et al, 2019) can improve learning of MI-BCI. Improving the training conditions might reveal a more robust difference between (in-)efficient learners and thereby provide more valid evidence for the impacting variables on MI-BCI.…”
Section: Future Researchmentioning
confidence: 99%
“…The ES tried to improve the AO effect; however, there were no statistically significant differences between the accuracies of the VIR and VER groups for most of the cases. The protocol proposed could be modified to improve BCI classification performance taking the advantages of the ES [28] to enhance the MI performance and attention [5], [15], [16], [47] during BCI calibration sessions.…”
Section: Discussionmentioning
confidence: 99%
“…It was evaluated for the two-class and three-class classification; the MI tasks were flexion, extension, and grasping, which are difficult to classify owing to the overlapped corresponded area on the motor cortex. In addition, we included VR animations as BCI training reinforcement after the MI task to contribute to the decoding enhancement, similar to feedback sessions [28]; visual reinforcement (VIR) is based on that action observation (AO) increased the ERD power, visual stimulation displaying body movements stimulates the motor-related cortical areas that correspond to the observed movement through the mirror neuron system [29]- [31]. Then, ES was added to visual reinforcement (VER) to provide proprioceptive stimulation without provoking muscle fatigue and contribute to MI learning, as mentioned previously; both types of reinforcements were compared.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Wilson et al [27] proposed a lingual electrotactile stimulation feedback as a vision substitution system in a BCI based on MI to move a cursor, where subjects with or without visual disability obtained similar results. Also, a BCI used visual-haptic feedback [28], which comprised a visual scene and electrical stimulation simultaneously. is feedback combination improved sensorimotor cortical activity and BCI performance during MI in able-bodied subjects.…”
Section: Introductionmentioning
confidence: 99%